A study of pathways to care among opioid dependent individuals seeking treatment at a community de-addiction clinic in India. Issue 3 (3rd August 2020) - Bhad, Roshan; Gupta, Rishab; Balhara, Yatan Pal Singh
Abstract: Drug use, including opioid use disorder, is one of the rapidly rising and serious problems affecting populations globally. There is a treatment gap and delay in presentation of drug users to treatment centers. The present study aimed at assessing the pathways to care among opioid-dependent individuals seeking treatment from a community-based treatment center in India. In a cross-sectional observational study conducted at a community clinic of the National Drug Dependence Treatment Centre (NDDTC), New Delhi, India, a total of 100 treatment-seeking drug users (age 18–60 years) fulfilling DSM IV TR criteria for opioid dependence were recruited. The data were collected using a semistructured pro forma based on patient self-report and the encounter form used in the World Health Organization (WHO) Pathway Study. All participants were male, were mostly married, were employed, and belonged to nuclear families. Ninety-eight percent of participants has ever used heroin in a dependent fashion and 20% were using it currently. Mean age of the participants was 40.83 years (SD 12.7). Median age of onset of heroin use was 22 years (IQR 12). Median duration of heroin use was 138 months (IQR 132). Only 21% of participants visited the community deaddiction clinic at the first contact with care. The median time for first treatment-seeking attempt was 9.5 years (IQR 7). The study findings suggest significant delay between onset of drug-related problems and first treatment contact. There is a need to increase the availability and accessibility of treatment services to reduce the delay in treatment seeking.